Care and social integration in European societies / edited by Birgit Pfau-Effinger and Birgit Geissler. - Pfau-Effinger, Birgit; Geissler, Birgit (Policy Press, 2005)
This book provides an overview and comparative analyses of the arrangements for the care of children, disabled and older people in Europe, within the context of changing labour markets and welfare systems. Gender, family change, social integration and citizenship are all explored in a report based on original empirical, cross-national research.